Luminescence of the Mn2+ ion in non-Oh and Td coordination environments: the missing case of square pyramid. Issue 43 (25th October 2019) - Artem'ev, Alexander V.; Davydova, Maria P.; Berezin, Alexey S.; Brel, Valery K.; Morgalyuk, Vasilii P.; Bagryanskaya, Irina Yu.; Samsonenko, Denis G.
Abstract : The luminescence of Mn 2+ ion in a square-pyramidal ( C 4v ) ligand field was discovered. The molecular complexes with such coordination geometry exhibit red emission with enhanced Stokes shift and millisecond lifetimes. Abstract : The first observation of luminescence for Mn(ii ) complexes with a square-pyramidal geometry ( C 4v ) of the metal is reported. The complexes of such type, namely [Mn(L)2 Hal]X, where L is an O, O′-chelating ligand Me2 N–CH(Ph2 PO)2, Hal = Cl or Br, and X = Br, I or [MnCl4 ], show at ambient temperature red photoluminescence ( λ emmax ≈ 620 nm) with millisecond lifetimes (3.8–7.6 ms). This emission, stemming from spin-forbidden 4 E(G) → 6 A1 (S) transitions in square-pyramidally coordinated Mn 2+, is found to be responsive to temperature. Upon cooling the complexes from 300 to 77 K, the red-shift of the emission band by ≈20 nm takes place, which is accompanied by the increase of its integral intensity and lifetime. The peculiarities of the discovered Mn 2+ ( C 4v ) luminescence are discussed against the classical luminescence that occurs in octahedral ( O h ) and tetrahedral ( T d ) surroundings.